A novel silicon graphite composite material with core‐shell structure as an anode for lithium‐ion batteries. Issue 4 (11th June 2020) - Yin, Ao; Yang, Lezhi; Zhuang, Zilong; Feng, Qingge; Liu, Zhikuan; Chen, Tao; Tu, Feiyue; Peng, Qinjiao; Luo, Lei; Tang, Gang; Chen, Wenqiang; Qin, Shibiao; et al.
Abstract: In this work, a novel core‐shell structure consisting of a porous graphite core, a nanosilicon filler layer, and a pitch coating carbon shell has been developed for lithium‐ion battery anode material. This structure was prepared by liquid‐phase milling and carbonization processes. Compared with other silicon (Si)‐based anode materials, this structure has a unique three‐dimensional conductive network consisting of conductive materials of conductive carbon, graphene, porous graphite, and carbon shell. The conductive network could effectively enhance the conductivity of the core‐shell structure. In addition, this structure was designed with moderate porous rate that provided nanosilicon appropriate expansion space. The coin cell test showed that this new material has a reversible capacity of 400 mA h g −1, retention of above 95% after 40 cycles, an initial columbic efficiency of 83.04%, and an average coulombic efficiency of above 99%. This novel material could have a great potential for future commercial application. The structure designed could be a possible solution for Si anode materials with low manufacturing cost and high performance.